Comparative study of 150 keV Ar+ and O+ ion implantation induced structural modification on electrical conductivity in Bakelite polymer. (February 2018) - Aneesh Kumar, K.V.; Krishnaveni, S.; Asokan, K.; Ranganathaiah, C.; Ravikumar, H.B.
Abstract: A comparative study of 150 keV argon (Ar + ) and oxygen (O + ) ion implantation induced microstructural modifications in Bakelite Resistive Plate Chamber (RPC) detector material at different implantation fluences have been studied using Positron Annihilation Lifetime Spectroscopy (PALS). Positron lifetime parameters viz., o-Ps lifetime (τ3 ) and its intensity (I3 ) upon lower implantation fluences can be interpreted as the cross-linking and the increased local temperature induced diffusion followed by trapping of ions in the interior polymer voids. The increased o-Ps lifetime (τ3 ) at higher O + ion implantation fluences indicates chain scission owing to the oxidation and track formation. This is also justified by the X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) results. The modification in the microstructure and electrical conductivity of Bakelite materials are more upon implantation of O + ions than Ar + ions of same energy and fluences. The reduced electrical conductivity of Bakelite polymer material upon ion implantation of both the ions is correlated to the conducting pathways and cross-links in the polymer matrix. The appropriate energy and fluence of implanting ions might reduce the leakage current and hence improve the performance of Bakelite RPC detectors. Graphical abstract: Highlights: 150 keV O + and Ar + ion implantation induced structural modifications in Bakelite polymer have been explored using PALS. Microstructural variations and conductivity is more upon O + ion implantation than Ar + ions of same energy and fluences. The electrical conductivity and free volume sizes at different fluences are well correlated. Appropriate energy and fluence of ion implantation enhances the strength of Bakelite polymer. The increased strength and surface resistivity improve the performance of Bakelite RPC detectors.